166k views
4 votes
Please help me with math!

Please help me with math!-example-1
User Jason Sims
by
4.9k points

1 Answer

3 votes

Answer:


(F_(f))/(m*g*cos(x)) =u

Explanation:

The statement says the following:


F_(f)= u*F_(N) \\F_(N)=m*g*Cos(∅)

We need to find 'u' given that we know the following terms:
F_(f), F_(N), m, g, ∅

The way to do that is to substitute not known expression into known expression, we will use the expression of
F_(N) in
F_(F)

This leads to


F_(f)=u*m*g*cos(∅)

Finally we can obtain 'u' by dividing the whole equation with the terms that are with 'u'

We have this


(F_(f))/(m*g*cos(x)) =u

Where 'u' is the variable that you are looking for

User ArtFeel
by
5.6k points